OSP-1 protects neurons from autophagic cell death induced by acute oxidative stress - Alessandra Donato; Fiona K. Ritchie; Lachlan Lu; Mehershad Wadia; Ramon Martinez-Marmol; Eva Kaulich; Kornraviya Sankorrakul; Hang Lu; Sean Coakley; Elizabeth J. Coulson; Massimo A. Hilliard (Nature Communications)
Abstract Oxidative stress, caused by the accumulation of reactive oxygen species (ROS), is a pathological factor in several incurable neurodegenerative conditions as well as in stroke. However, our knowledge of the genetic elements that can be manipulated to protect neurons from oxidative stress-induced cell death is still very limited. Here, using Caenorhabditis elegans as a model system, combined with the optogenetic tool KillerRed to spatially and temporally control ROS generation, we identify a previously uncharacterized gene, oxidative stress protective 1 (osp-1), that protects C. elegans neurons from oxidative damage. Using rodent and human cell cultures, we also show that the protective effect of OSP-1 extends to mammalian cells. Moreover, we demonstrate that OSP-1 functions in a strictly cell-autonomous fashion, and that it localizes to the endoplasmic reticulum (ER) where it has an ER-remodeling function. Finally, we present evidence suggesting that OSP-1 may exert its neuroprotective function by influencing autophagy. Our results point to a potential role of OSP-1 in modulating autophagy, and suggest that overactivation of this cellular process could contribute to neuronal death triggered by oxidative damage.